Hematologic and biochemical reference intervals for adult Friesian horses from North America. (26th February 2015) - Sample, Saundra H.; Fox, Katherine M.; Wunn, Denise; Roth, Elizabeth; Friedrichs, Kristen R.
<x xml:space="preserve">Abstract</x> Background Established breed‐specific reference intervals (RI) are an important tool for monitoring the health of horses. There is a lack of published work on breed‐specific RI for Friesian horses. Objectives The goal of this project was to determine hematologic and biochemical RI for Friesian horses residing in North America. Methods Strict inclusion and exclusion criteria were established for selection of reference subjects and for blood specimen collection and handling. Blood samples from 123 healthy, adult (range 3–18 years, median 8 years) Friesian horses of both sexes (70 mares, 45 geldings, and 8 stallions) were used to determine RI. Complete blood counts (CBC) and biochemistry profiles were performed on the Sysmex XT‐2000iV hematology and Olympus AU400 biochemistry analyzers, respectively, at IDEXX Laboratories Inc. (Columbus, OH, USA). Results were analyzed using Reference Value Advisor. According to the guidelines of the ASVCP, nonparametric RI with 90% confidence intervals were determined. Results IDEXX equine RI are transferrable to Friesian horses for 30 of 36 analytes. Friesian‐specific RI (medians) are recommended for the following variables: RBC 5.02–8.74 × 106/μL (6.66), HCT 27–42% (34), HGB 9.0–14.3 g/dL (11.4), lactate dehydrogenase 299–866 U/L (493), direct bilirubin 0.3–0.7 mg/dL (0.5), and anion gap 7–18 mEq/L (12). Conclusions The RI established in this study provide a useful baseline for the assessment of hematologic and biochemical data in Friesian horses residing in North America.